Menemukan Makna Aurat Dalam Tafsir Al-Qur’an Klasik Dan Ontemporer - Emawati Emawati (Universitas Islam Negeri Mataram, 2006)
Elucidating meaning of a term which later develops to be a concept need a comprehensive understanding and depth knowledge of the term. Genital (awrât, aurat) which arises to be a debatable concept needs reconsideration in its meaning which recently merely associated with the female rather than the male. For that reason, this writing, with its limitation, is trying to explore the comprehensive meaning of genital which is mentioned four times in the holy Qur’an in three verses—al-Ahzâb (33):13, al-Nûr (24): 58 and al-Nûr (24): 31. The exploration of meaning of the verses here will be focused on the meaning given by three experts in their books namely al-Qurthûbî, al-Marâghî and Quraish Shihab. However, for the aim of getting closer to the perfectness, this writing is also supported by the idea of some modern experts to see how genital is perceived according to the socio-culture of the society.